Strategic Processing of Chinese Young English Language Learners in an International Standardized English Language Test - Han, Feifei (Frontiers in Psychology, 2018)
Strategic competence is acknowledged to be able to explain variations in language test performance. Research with adult language test-takers has shown that strategic competence has dual components: strategic knowledge and strategic processing. Of the two components, strategic processing, which is state-like, unstable, and tends to fluctuate from contexts to contexts, is more closely related to language test performance. To date, none of the existing studies investigates strategic processing with children English language learners (ELLs) and explores the relationship between strategic processing in all the four skills of language learning and the test performance. Addressing these gaps, the current study examined the nature of strategic processing in listening, reading and writing, and speaking of 138 Chinese young ELLs in an international standardized English language test – Cambridge Young Learners English Tests – Flyers test. The three questionnaires regarding strategic processing were administered to the participants immediately following the completion of the test. The confirmatory factor analyses verified that the strategic processing construct in the four skills comprised of a cognitive and a metacognitive dimensions, which resembles the strategic processing of the adult language test-takers. The participants adopted significantly more metacognitive than cognitive strategies consistently in the three sections of the test, possibly due to the status of the test. Both cognitive and metacognitive strategic processing were moderately related to the test performance, explaining from 7 to 31% of the variance in the total shields of the test. Across the four skills, high-performing test-takers used both cognitive and metacognitive strategies more frequently than the moderate- and low-performing test-takers, even though whether such differences were due to their richer strategic knowledge or processing skills was unknown. The study contributes to strategic processing in language testing literature and also provides practical implications for English trainers of the young ELLs in China.